Exploring EFL Learners’ Difficulties in Academic Writing: Problem and Solution - Rita Handayani (Journal of Linguistics, Literacy, and Pedagogy, 2023)
For EFL students at universities, writing an effective paragraph is essential to their academic and eventual professional success. To teach and learn this skill, though, is never easy for either the teacher or the student. This study aims to uncover the challenges that EFL Indonesian university students have while writing an effective paragraph and to propose solutions to those challenges. A qualitative approach to data collecting and analysis was used to accomplish the research objectives, and data was gathered through the paragraph writing exam, questionnaire, and classroom observations. The examination of the students' paragraph writing found that the crucial difficulties encountered by the students in writing a well-developed paragraph were developing the topic phrase (70%), as well as focusing and organizing their thoughts.